Model structures amplify uncertainty in predicted soil carbon responses to climate change - Zheng Shi; Sean Crowell; Yiqi Luo; Berrien Moore (Nature Communications, 2018)
A substantial portion of model uncertainty arises from model parameters and structures. Here, the authors show that alternative model structures with data-driven parameters project greater uncertainty in soil carbon responses to climate change than the conventional soil carbon model.